Peran Negara dalam Sekuritisasi Politik Identitas: Studi Komparatif Konflik Rohingya dan Palestina-Israel - Zulfikar, Muhammad (Jurnal Hubungan Internasional Indonesia, 2025)
This article examines the role of the state in shaping identity politics that lead to violence, through comparative case studies of the Rohingya conflict in Myanmar and the Israel-Palestine conflict. Using the theoretical framework of securitization and identity politics, this qualitative comparative research analyzes how governments in both cases construct certain identity groups as security threats. The findings indicate that in both Myanmar and the Israel-Palestine conflict, state actors actively engaged in “securitization”, portraying ethnic or religious minority identities as existential threats, to justify repressive policies and violence. In Myanmar, the regime mainstreamed a narrative of threat to Buddhist national identity to legitimize the repression and ethnic cleansing of the Rohingya. Meanwhile, in the Israel-Palestine conflict, the State of Israel emphasizes the state’s Jewish identity and securitizes the Palestinian population as a threat, resulting in military occupation and human rights violations. The study concludes that identity politics securitized by the state can fuel violent conflict and neglect the human security of oppressed groups. These findings contribute to the understanding of identity conflicts, state violence, and human security in international relations by elucidating linkages between state-driven identity construction, securitization, and violence against minorities. Keywords: Identity Politics, Securitization, State Violence, Rohingya, Israel-Palestine, Human Security